A mini-review focusing on ambient-pressure chemical vapor deposition (AP-CVD) based synthesis of layered transition metal selenides for energy storage applications. Issue 11 (19th May 2022) - Konar, Rajashree; Nessim, Gilbert Daniel
Abstract : 2D layered transition metal selenides grown in ambient pressure CVD for promising energy storage applications. Abstract : With high power consumption and energy densities in demand, there has been a surge in the research on next-generation electrochemical energy storage devices (lithium-ion batteries (LIBs), sodium-ion batteries (NIBs), and magnesium-ion batteries (MIBs)). 2D layered transition metal selenides (TMSes) are promising in terms of scalability and portability for electronic devices and electric vehicles. Such large-scale applications rely on exploring these TMSes containing high capacity, good cycling stability, and superior rate capability. Their exotic anisotropic properties have pushed their research towards energy storage. Since chemical vapor deposition (CVD) is an efficient and scalable technique to synthesize these materials, we summarize the synthesis of TMSes using ambient-pressure CVD and highlight their many properties, preparation methods, and applications in LIBs, NIBs, and MIBs. We discuss how tuning surface morphology dominates the reaction kinetics. This review finally discusses the challenges and opportunities of these materials in terms of modifications in synthesis and their constant applications in the ever-growing field of energy storage.